Performance Appraisals and the Impact of Forced Distribution—An Experimental Investigation - Berger, Johannes; Harbring, Christine; Sliwka, Dirk (Management Science, 2013)
A real-effort experiment is investigated in which supervisors have to rate the performance of individual workers who in turn receive a bonus payment based on these ratings. We compare a baseline treatment in which supervisors are not restricted in their rating behavior to a forced distribution system in which they have to assign differentiated grades. We find that productivity is significantly higher under a forced distribution by about 6% to 12%. However, the productivity effects are less clear cut when participants have prior experience with the baseline condition. Moreover, a forced distribution becomes detrimental when workers have access to a simple option to sabotage each other. This paper was accepted by Peter Wakker, decision analysis.